Poetry as resistance - Langah, Nukhbah Taj, author.
1 online resource (xxiii, 271 pages)
Keywords: Focusing on the culturally and historically rich Siraiki-speaking region, often tagged as South Punjab', this book discusses the ways in which Siraiki creative writers have transformed into political activists, resisting the self-imposed domination of the Punjabi-Mohajir ruling elite. Influenced by Sufi poets, their poetry takes the shape of both protest and dialogue. This book reflects upon the politics of identity and the political complications which are a result of colonisation and later, neo-colonisation of Pakistan. It challenges the philosophy of Pakistan -- a state created for Muslims -- which is now taking the shape of religious fanaticism, while disregarding ethnic and linguistic issues such as that of Siraiki.